DESAIN MODEL PEMBELAJARAN GERLACH DAN ELY YANG BERCIRI NILAI-NILAI KE-ISLAMAN UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS - Reza Setiawati; Netriwati Netriwati; Sri Purwanti Nasution (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The low mathematical communication skills in SMA 2 Natar, South Lampung, are caused by various factors, including the assumption that mathematics is very difficult so students still tend to be passive. The purpose of this study was to determine the mathematical communication skills of students who used the Gerlach and Ely learning models that characterized Islamic values better than conventional learning. The population in this study were students of class X Natar 2 Public High School. This research is a pre-experimental design with one-group pretest-posttest type. The test prerequisite analysis was done by Liliefors test for normality and F test for homogeneity, then the data were analyzed using N-Gain test and correlated t-test. The results of the analysis in the t-test test correlates mathematical communication skills in the material of the nilier equation system three variables at the significance level α = 0.05 obtained by tcount = 24.19 Ttable = 2.045 24, Thitung> T table so that in the calculation of H0 is rejected. Similarly, mathematical communication skills can be improved after using the Gerlach and Ely learning model characterized by Islamic values on the subject of the three-variable linear equation system